IMPLEMENTASI PEMEBELAJARAN ASWAJA DI MTs MU’ALLIMIN NU MALANG - Achmad Ali Mansur (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the application of Aswaja learning at the MTs Mu'allimin NU Malang. The problems that exist are students who do not understand religious studies especially Aswaja subjects, because of lack of motivation from the family. The data in this study were obtained from teachers and several students. This study uses a qualitative method. Documents obtained from interviews, observations, and documentation. Then the data is captured and displayed until it draws conclusions and verifies conclusions. The conclusion of the research shows that the teacher carries out 3 stages, namely, planning, implementation, and evaluation. So that the teacher can be maximal in implementing the Aswaja subjects.Keywords : Implementation, Learning, Aswaja